Localizing Norms in Indonesia: The Role of Islamic Family Law in Achieving SDG 5 and 16 - Siti Nurul Aina Safika; Nurhidayat; Khaerunnisa, Khaerunnisa; Iswan, Iswan; Asdar, Asdar (proceedings.icesy, 2026)
This article examines how Sustainable Development Goal (SDG) 5 (gender equality) and SDG 16 (access to justice and effective institutions) are localized within Indonesia’s Islamic family law through the architecture of norms and the adjudicative practices of the Religious Courts. Using doctrinal legal research, it combines statute and conceptual approaches with a case law analysis of selected Religious Court decisions on marriage dispensation, divorce and post-divorce maintenance (iddah and mut’ah), child custody, and polygamy. The analysis maps the normative chain from constitutional guarantees of equality and due process to family legislation, the Compilation of Islamic Law, and Supreme Court procedural instruments that shape access, proof, and remedies. Findings show that localization occurs primarily at the level of adjudication through three recurring reasoning patterns: formalist legalistic decisions that treat SDG relevant harms as administratively manageable; purposive protective decisions that mobilize maqāṣid al-sharīʿa and constitutional rights to prioritize protection of women and children; and procedural pragmatic decisions that privilege efficiency and settlement, sometimes at the expense of safety and equality. Across case types, the decisive indicator of substantive rule of law is the quality of remedies and protective orders when economic relief, custody arrangements, and procedural safeguards are reasoned, proportionate, and enforceable, courts contribute simultaneously to SDG 5 and SDG 16. The article contributes a doctrinal framework that operationalizes the SDGs as justiciable evaluative parameters, identifies points of normative disharmony and discretion driven gaps, and proposes standards for violence screening, evidence assessment, and remedial consistency to strengthen gender equal access to justice in Indonesia’s plural order.